Rational Man A Modern Interpretation of Aristotelian Ethics - Veatch, Henry B. (Indiana University Press, 1962)
"God is dead," proclaimed Nietzsche; meaning that neither nature nor the supernatural can provide any solid ground on which to base rules or standards of human conduct. To this dictum, which is consciously or unconsciously accepted by many people today, the author of this book takes strong exception. There are, he believes, rational grounds for ethical standards, for an "art of living" the good life; and he defends this thesis with arguments derived from the great Greek philosophers but focused on problems of modern living. Writing in non-technical language, the author acknowledges his debt to Aristotle (and also Socrates and Plato), but his purpose is not merely to restate Aristotle's ideas but "to use him in a modern effort to set forth and justify a rational system of ethics." Mr. Veatch makes short shrift of modern philosophical writers who merely analyze the language of ethics but disclaim any concern with its content, and he vigorously refutes objections to his position made by relativists, behaviorists and utilitarians. Existentialists, on the other hand, he finds closer to the search for a rational ethic than is commonly supposed. While his discussion centers on ethics, he acknowledges the important role of religion in human conduct. Thoughtful readers and students will welcome this attractive and intelligible presentation of the case foe a realistic ethics in modern life.